(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Managing solid waste is a significant issue in many industrialized and developing nations. The greatest and priciest component of waste management is solid waste collection. The improvement of collecting solid waste is very important because of its overall cost reduction and positive environmental impacts. This paper reviews the impact of using GIS-based improvement techniques for solid waste collection. The optimization process using GIS is unique compared to other solid waste collection optimization techniques that provide temporary solutions when applied. GIS provides room for additional parameters to be addressed during the optimization process, including street modeling. GIS has proven its efficiency in optimizing solid waste collection through shortest path selection using the Dijkstra algorithm and modeling processes using model builder.